Behind political affiliation: How moral values, identity politics, and party loyalty have affected COVID-19 vaccination - Piergiuseppe Fortunato; Alessio Lombini (PLoS ONE, 2025)
Falling short of its vaccination goals, the United States faced a critical challenge in ending the pandemic, with political partisanship emerging as a barrier to COVID-19 vaccination uptake. This study investigates the relationship between partisanship, moral values, and vaccination compliance in 3099 US counties during the vaccination campaign, employing descriptive statistics and panel regressions. The findings reveal that the relationship between political partisanship and vaccination uptake varies highly when considering three factors: historical party rootedness, party factions, and co-partisan state governors. We report a widening vaccination rate gap between Republican and Democratic counties, particularly when considering the historical partisanship of a county. Our analysis also reveals that Republican counties with strong support for Trump had vaccination rates that were 2% to 5.9% lower than those observed in Republican counties with low support for Trump. Importantly, moral values significantly mediate the association between partisanship and vaccination compliance. High levels of communal values reduce the predictive power of partisanship and strong support for Trump in explaining vaccination rates by up to 56% and 80%, respectively. The presence of a co-partisan state governor was linked to approximately 3.5% higher vaccination rates in Republican counties and 3.1% higher rates in Democratic-leaning ones. This study demonstrates that the factors explaining vaccine compliance extend beyond dichotomous political orientation. The role of individual moral values is significant in this context. To be most effective, vaccination campaigns—and corresponding messages—should be tailored to reflect the moral and partisanship milieu of their target demographics. The involvement of political leaders, especially in Republican-leaning areas, emerges as a key strategy for increasing vaccine acceptance among these groups.